2018
DOI: 10.20944/preprints201808.0025.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health and Aging: Unifying Concepts, Scores, Biomarkers and Pathways

Abstract: Despite increasing research efforts, there is a lack of consensus on defining aging or health. To understand the underlying processes, and to foster the development of targeted interventions towards increasing one’s health, there is an urgent need: (1) to find a broadly acceptable and useful definition of health, based on a list of features (which may or may not be molecular); (2) to operationalize features of health so that it can be measured; (3) to identify predictive biomarkers and (molecular) pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The process of aging involves most (if not all) aspects of life and in molecular terms, it thus involves a wide variety of signaling pathways at least to some degree. Aging is considered to be the causal process underlying age-associated disease and dysfunction (Fuellen et al, 2019). Accordingly, increasing chronological age is the foremost risk factor for the development of all kinds of chronic diseases such as type 2 diabetes, cardiovascular disease, osteoporosis, arthritis, Alzheimer’s disease and cancer, along with age-associated dysfunction such as frailty and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The process of aging involves most (if not all) aspects of life and in molecular terms, it thus involves a wide variety of signaling pathways at least to some degree. Aging is considered to be the causal process underlying age-associated disease and dysfunction (Fuellen et al, 2019). Accordingly, increasing chronological age is the foremost risk factor for the development of all kinds of chronic diseases such as type 2 diabetes, cardiovascular disease, osteoporosis, arthritis, Alzheimer’s disease and cancer, along with age-associated dysfunction such as frailty and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike lifespan, which has a universal definition, there is no consensus on the definition of healthspan 5,6 . Previous research has suggested characterizing healthy aging in five domains: physical capability, cognitive function, physiological and musculoskeletal, endocrine, and immune functions 5,7 .…”
Section: Mainmentioning
confidence: 99%
“…However, the continuous increase in life expectancy, paired with an unchanged age of the onset of morbidity and ageing-associated diseases (Crimmins 2015) highlights that lifespan is not representative for the various phenotypes of ageing. Thus, the focus is increasingly on health and healthspan, defined by the lack of diseases and dysfunctions addressing physiological, physical, cognitive, and reproductive functions (Fuellen et al 2019).…”
Section: Introductionmentioning
confidence: 99%